Estimating Value of The Firm for Telecommunication Company (Case Study Telecommunication Companies: PT Telekomunikasi Indonesia, PT XL Axiata, PT Indosat, and PT bakrie Telecom in Indonesia) - Arifin, Ahmad Faris; Anggono, Achmad Herlanto (Journal of Business and Management, 2012)
Telecommunication has become the primary choice for communicating indirectly and has been use by every level of society. In Indonesia, phones have become the major factor of everyday life and the backbone of economic growth. In Indonesia, phone operators are growing fast every year and now, there are four major telecommunication company in Indonesia which are PT Telekomunikasi Indonesia, PT XL Axiata, PT Indosat, and PT Bakrie Telecom.However, the trends and estimation towards the industry in the next five years suggest that the revenue will decrease because of the decreasing trends of the Average Revenue Per User (Arpu) rate. To keep the business going and gain a growth on the revenue, an operator needs to develop new strategy. An operator needs to clarify their strength and persuade customer to use more of their services to increase the usage and the ARPU. To this date, operators competing to create a newValue Added Service and bringing new technology to Indonesia such as NFC (Near Field Communication), Cloud System, and LTE (Long Term Evolution) 4G network.To apply those new technologies and keeping growth on the company, operator needs a lot of money to be invested. Bank and private investors will be happy to invest their money only if they know that the investment will be paid back. To make a guarantee for the investors, a company will calculate their value in the future. It will appeal investors to invest in the company, and whoever have a higher value, they usually will lead the competition. That’s why, the calculation of the value for each company is necessary in order to see the position of the company in the market as well as the performance itself.This research will calculate the value of four different company in Indonesia telecommunication industry, the rank of company’s value, and each company’s condition whether it’s share price is undervalued or overvalued. After calculating the value of other company, with a condition that PT Bakrie Telecom cannot be measured in this research because of its negative earnings, it turns out that XL Axiata and Indonesia have a current share price inside of the price range, while Telkom Indoneisa has a current share price below the price range. Telkom Indonesia is undervalue from both market approach and income approach perspective.Keywords: Telkom Indonesia, Bakrie Telecom, XL Axiata, Indosat, value, valuation, estimation, assumption, discounted cash flow, p/e ratio, scenario.Category: Finance; Business Strategy.